Psychiatric-mental health nursing - Videbeck, Sheila L.; Miller, C. J. (Cathy J.) (Philadelphia, PA : Wolters Kluwer, 2023)
"Created specifically to appeal to students' preferences and favored for its clear, practical approach and engaging learning features, Psychiatric-Mental Health Nursing, 9th Edition, makes the full spectrum of psychiatric nursing easier to understand and equips students with a confident grasp of the skills and concepts essential to their success in clinical practice. This 9th Edition has been extensively revised throughout, reflecting the latest evidence-based perspectives and practices while maintaining a strong foundation in the nursing process." -- Publisher
Foundations of psychiatric-mental health nursing -- Neurobiologic theories and psychopharmacology -- Psychosocial theories and therapy -- Treatment settings and therapeutic programs -- Therapeutic relationships -- Therapeutic communication -- Client's response to illness -- Assessment -- Legal and ethical issues -- Grief and loss -- Anger, hostility, and aggression -- Abuse and violence -- Trauma and stressor-related disorders -- Anxiety and anxiety disorders -- Obsessive-compulsive and related disorders -- Schizophrenia -- Mood disorders and suicides -- Personality disorders -- Addiction -- Eating disorders -- Somatic symptom illnesses -- Neurodevelopmental disorders -- Disruptive behavior disorders -- Cognitive disorders
Includes bibliographical references and index
Keywords: Psychiatric nursing; Nurse and patient; Psychiatric Nursing; Mental Disorders -- nursing; Nurse-Patient Relations